2002
DOI: 10.1002/jso.10049
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of p53, Ki‐67, and c‐erbB‐2 in phyllodes tumors of the breast in correlation with clinical and morphologic features

Abstract: p53 expression tends to be more frequent in PT with higher malignant potential but did not predict recurrence. Incompletely excised tumors that recurred displayed high proliferative activity in their primary tumors. Progression toward more malignant phenotype in the recurrent PT was accompanied with increase in stromal cell proliferative activity, suggesting the presence of biological continuity between benign, borderline, and malignant PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
0
23
1
1
Order By: Relevance
“…Shpitz et al has reported that the expression of p53 tends to be higher in phyllodes tumors of higher malignant potential. 46 Thus, it is possible that heparan sulfate may cooperate with p53 in regulating cell cycle progression in phyllodes stromal cells. Also, the epithelial expression of bcl2, a well-known antiapoptotic protein, is decreased in malignant phyllodes tumors with little or no 10E4 staining.…”
Section: Discussionmentioning
confidence: 99%
“…Shpitz et al has reported that the expression of p53 tends to be higher in phyllodes tumors of higher malignant potential. 46 Thus, it is possible that heparan sulfate may cooperate with p53 in regulating cell cycle progression in phyllodes stromal cells. Also, the epithelial expression of bcl2, a well-known antiapoptotic protein, is decreased in malignant phyllodes tumors with little or no 10E4 staining.…”
Section: Discussionmentioning
confidence: 99%
“…In phyllodes tumors there is increased p53 protein expression in higher-grade lesions compared with lower-grade lesions [3,[18][19][20], and the staining pattern in malignant phyllodes tumors, and very occasionally in borderline tumors, is characteristically diffuse strong nuclear staining, particularly in the high cellularity area and in the sub-epithelial location [3]. p53 has been shown to be associated with atypia, tumor grade, prominent stromal overgrowth, mitotic count, stromal nuclear pleomorphism, high stromal mitotic count, and an infiltrative margin [3,19,[21][22][23]. Most studies however were unable to demonstrate the ability of p53 to predict outcome or recurrence [3,19,22], although one series suggested that increased p53 expression in phyllodes tumors correlated with worse disease or recurrence-free survival [24].…”
Section: Biological Markersmentioning
confidence: 96%
“…Studies have shown that p53, Ki67, CD117, 34,35 EGFR, 36 p16, 37 and VEGF 38 (being the lowest in benign PT and the highest in malignant PT) are associated with histologic grades of PT, but none has been proven to be clinically useful. Among these markers, p53 expression and Ki67 index were reported in some studies 39,40 to be significantly associated with disease-free and overall survivals, but other studies 41,42 found no association with recurrence or clinical behavior. PAX3 and SIX1 expression by immunohistochemistry 43 and gene-expression analysis 44 has recently been identified in borderline and malignant PTs and correlates with a poor clinical outcome.…”
Section: Molecular/genetic Featuresmentioning
confidence: 98%